The process of managing medical solid waste at the Siti Hajar Islamic Hospital Sidoarjo - Ika Fahraeni Arifah; Permadina Kanah Arieska (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Management of medical solid waste is very important, especially for health providers and the general public who are beginning to be aware of the effects of bad waste management and become a major threat to public health. This study aims to analyze the process of managing medical solid waste at RSI SH Sidoarjo based on the Minister of Health Decree No. 1204 of 2004 concerning hospital environmental health requirements. The type of research used is descriptive qualitative. The study was conducted form February to March 2019 with a total of 7 informants. Data collection by observation, interview and document study. Data analysis used the method of source triangulation and theory triangulation. The results showed that, of the 6 aspects of medical solid waste management there were 3 aspects which were entirely (100.0%) optimally implemented, namely the aspect of sorting, storage and destruction, in the aspect of collection and transportation mostly (75.0% and 66.8% ) optimally implemented, the half of the TPS aspect (50.0%) was carried out optimally. It is recommended to collect aspects to adjust the use of safety boxes in each room. In the aspect of transportation, make a policy related to the use of PPE for cleaning service officers who handle medical solid waste and rearrange the transportation routes. In the aspect of TPS, reuse incinerators to treat medical solid waste.